Regional Differences in the Intergenerational Transmission of Family Size in Europe. Issue 2 (25th November 2015) - Mönkediek, Bastian; Rotering, Paul; Bras, Hilde
Abstract: Many studies report positive correlations between family sizes of successive generations, but the degree of correlation varies between countries. However, the majority of these studies are limited in geographical scope and do not consider the role of regional family organisation principles, that is, family systems. In this paper, we investigate to what extent regional family systems explain geographical differences in intergenerational transmission of family size among European regions. Using the large‐scale European Survey of Health, Ageing and Retirement in Europe, we derive indicators of regional family systems based on average frequency of contact and geographical distance between kin. We use a multilevel random coefficients model to test for differences in the transmission between European regions, as well as between sons and daughters. We find a complex regional pattern of family influences on childbearing continuities, with considerable within‐country variation. We observe a direct effect of parental fertility on offspring fertility, although sons show more variance than daughters. This transmission of fertility can be attributed to regional family systems for sons, but not for daughters. Our results demonstrate the importance of using a regional approach –rather than the country‐level approach –to study intergenerational continuities in childbearing. Copyright © 2015 John Wiley & Sons, Ltd.